APPLICATION OF ELEMENTS OF ILLEGAL ACCESS CRIMINAL ACT VIA SOCIAL MEDIA BY INVESTIGATORS AT THE DIRECTORATE OF SPECIAL CRIMINAL INVESTIGATION OF THE WEST SUMATERA REGIONAL POLICE - Putra, Muhammad Subran Ardatul; Winjaya Laksana, Andri (Jurnal Hukum Khaira Ummah, 2024)
The more advanced the development in the field of technology, the more crimes appear, one of which is in the cyber world. Information Security and Electronic Transactions (ITE) is currently always overshadowed by the high level of ITE crimes, causing many people to become victims of cyber crimes. This study aims to determine the application of elements of the crime of illegal access through social media by investigators at the Ditreskrimsus Polda Sumbar. In this study, the approach method used is: a normative legal approach or an approach through literature study. The research specification used is Descriptive Analytical, which is an effort to analyze and explain legal problems related to objects with a comprehensive and systematic description of everything related to the application of elements of the crime of illegal access through social media by investigators at the Ditreskrimsus Polda Sumbar. The Application of Elements of the Crime of Illegal Access Through Social Media by Investigators at the Ditreskrimsus Polda Sumbar is by applying the elements contained in Article 35 of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Transaction Information. Obstacles in the Application of the Elements of the Criminal Act of Illegal Access via Social Media by Investigators at the Directorate of Special Criminal Investigation of the West Sumatra Regional Police, especially in terms of collecting evidence to fulfill the elements of the crime.